Pharmacist impact on medication reconciliation of behavioral health patients boarding in the emergency department - Mary Accomando, PharmD, BCPP; Kyle DeWitt, PharmD, BCPS; Blake Porter, PharmD, BCPS (American Association of Psychiatric Pharmacists, 2022)
Introduction: The high demand for psychiatric services has exceeded the capacity of available resources for behavioral health patients, forcing these patients to seek mental health care in the emergency department. Average lengths of stay for behavioral health boarders commonly extend over multiple days and prior-to-admission (PTA) medication administration may be delayed, which could lead to further deterioration and longer inpatient lengths of stay. Addition of a pharmacist-led medication reconciliation process and pharmacist integration into daily emergency department psychiatry rounds may decrease time to initiation of PTA medications and improve outcomes in this population. Methods: This is a retrospective review of adult patients who required a psychiatric emergency evaluation in a large rural academic medical center emergency department. Objectives were to determine the number and type of medication discrepancies found with pharmacist intervention, and to compare time to initiation of PTA medications with a pharmacist versus a nonpharmacist completing medication reconciliation. Results: A total of 139 patients were identified, 85 patients in August 2019 (no pharmacist [NP]) and 54 in October 2019 (pharmacist involvement [PI]). Among 484 medications reviewed in the PI group, 298 discrepancies were identified. The most common types of discrepancies were no longer taking (n = 99, 33%) and omission (n = 94, 32%). Time to administration of PTA medications was similar between NP and PI groups (median hours, interquartile range: NP: 10.8, 7.8-16.57; PI: 11.49, 6.16-16; P = .179). Discussion: This study depicted one of the many values of pharmacists in the hospital setting, especially in the behavioral health patient population where continuation of accurate PTA medications may prevent further clinical deterioration.